Evaluating the Effect of Flame for the Determination of Carbohydrate, Protein, and Dietary Fiber in Nepali Food Dhindo-Novel Food for Diabetic. (8th September 2020) - Sharma, Hemraj; Pudasaini, Puja; Dhungana, Saraswati; Pokharel, Manisha; Subedi, Punam; Sharma, Bedraj
Abstract : Dhindo is a thick pasty Nepalese porridge prepared by cooking grounded, millet, or cornmeal flour. It is a staple meal in various parts of Nepal, especially in hilly areas. It is prepared by gradually adding flour to boiling water while stirring. Due to its soft pasty nature, it can be eaten by any age of people; in particular, it is good for old age people. As majority of the world population has been suffering from diabetes and dhindo being believed to have less carbohydrate content, hence, this study can serve as great nutritional value to a large number of diabetic patients. The present study was undertaken to determine nutrient contents from the novel food dhindo, which is prepared from different flours (maize, wheat, millet, and buckwheat) and to compare its nutrients with rice. Dhindo and rice were prepared and analyzed for total carbohydrate, reducing sugar, protein, and fiber. Here, we compared all the nutrients of dhindo and rice as well as determined the effect of heat on the contents of dhindo and rice. Dhindo and rice were cooked, and all the samples were evaluated for the nutritional contents. Dietary fiber was determined from the gravimetric method. The millet form of dhindo contained a high amount of dietary fiber, which was found to be 0.835 gm by the firewood method and 0.82 gm by LPG gas. Total carbohydrate, reducing sugar, and protein were determined from the UV visible spectrophotometer. Rice contained a high amount of total and reducing sugar and was found to be 31.8 mg/3 gm and 30.03 mg/3 gm by LPG and firewood, respectively, for total carbohydrates and 0.218 mg/3 gm and 0.214 mg/3 gm by LPG and firewood, respectively, for reducing sugars. The protein was found to be maximum in the buckwheat form of dhindo, which was 15.892 mg/1 gm and 15.375 mg/1 gm by LPG and firewood, respectively. From this study, we can conclude that consuming dhindo would be advantageous for a diabetic patient than rice.